1998
DOI: 10.1029/98jb02049
|View full text |Cite
|
Sign up to set email alerts
|

Convective fluid flow through heterogeneous country rocks during contact metamorphism

Abstract: Abstract. Geochemical and petrologic data from contact aureoles consistently document fluid focusing through small-scale permeable structures. We use stochastic representations of permeability in a series of transient numerical simulations to assess how such smallscale rock heterogeneities influence kilometer-scale fluid convection around a shallow crustal pluton. The sensitivity study considers different permeability scenarios by varying statistical characteristics of the permeability distribution (mean, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 76 publications
1
43
0
Order By: Relevance
“…Their results point to significant time-integrated fluxes (5000 -300 mol/cm²) consistent with the order of magnitude published in previous studies (Ferry, 1994a). Thermal and hydrological numerical models constitute another approach to constrain the direction and amount of fluid flow (Norton and Knight, 1977;Hanson et al, 1993;Gerdes et al, 1998;Cui et al, 2001;Oliver et al, 2006). In some case, good agreement is found between predictions from numerical models and studies based on mineralogical and stable isotope data (e.g.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Their results point to significant time-integrated fluxes (5000 -300 mol/cm²) consistent with the order of magnitude published in previous studies (Ferry, 1994a). Thermal and hydrological numerical models constitute another approach to constrain the direction and amount of fluid flow (Norton and Knight, 1977;Hanson et al, 1993;Gerdes et al, 1998;Cui et al, 2001;Oliver et al, 2006). In some case, good agreement is found between predictions from numerical models and studies based on mineralogical and stable isotope data (e.g.…”
Section: Introductionsupporting
confidence: 75%
“…For active regional metamorphism, a Darcy velocity of 10 -11 m/s is considered to be an average value . Hydrothermal numerical models of contact or regional metamorphism, predict Darcy velocities ranging from 10 -8 m/s to 10 -11 m/s (Oliver et al, 2006;Gerdes et al, 1998;Cook et al, 1997). In this work, the calculated velocity at grain scale is much higher, about 10 -3 to 10 -4 m/s.…”
Section: Velocity Analysis and The Role Of Deformationmentioning
confidence: 60%
“…other similar studies [41,78], whereas McKenna and Blackwell indicate a maximum velocity value of 3.7 × 10 −10 m/s, generally too low to disturb significantly a thermal field (see the detailed numerical models by López and Smith [78], where significant distortion of the thermal field is obtained for velocity around 10 −7 m/s). In our numerical scheme being identical as in other studies [79,80] where other benchmark tests were performed [81,82], we validate our benchmark test of the Dixie Valley hydrothermal system.…”
Section: Numerical Modelingmentioning
confidence: 50%
“…Previous studies using convection-type models have shown the significant impact of anisotropy on flow patterns and heat transfer (Dutrow et al, 2001;Gerdes et al, 1998;Hurwitz et al, 2002Hurwitz et al, , 2003López and Smith, 1996;Rosenberg et al, 1993).…”
Section: Methodsmentioning
confidence: 99%